Dampak CSR dan ESG Terhadap Kinerja Keuangan dan Keberlanjutan Perusahaan Dimediasi oleh Green Finance - Fransisca, Linda; Helma Malini; Anwar Azazi; Anggraini Syahputri (Forum Kerjasama Pendidikan Tinggi, 2025)
The manufacturing sector plays a vital role in the global economy but is often linked to environmental and social harm. This has driven companies to adopt sustainable practices through ESG and CSR, funded in part by green finance. This research investigates the connection between ESG and CSR implementation with financial performance and sustainability, alongside the mediating role of green finance. Using panel data from 48 BEI-listed manufacturing firms (2021-2023), resulting in a total of 108 observations after outlier removal. Multiple regression analysis and the Sobel test are used to test the hypotheses. The analysis shows CSR positively affects financial performance but not sustainability, while ESG negatively impacts financial performance but positively influences sustainability. The sobel test reveals green finance mediates CSR’s effect on financial performance but not ESG’s.